Impact of obesity on robotic‐assisted surgery in patients with stage IA endometrial cancer and a low risk of recurrence: An institutional study. Issue 12 (15th September 2022) - Asanoma, Kazuo; Yahata, Hideaki; Okugawa, Kaoru; Ohgami, Tatsuhiro; Yasunaga, Masafumi; Kodama, Keisuke; Onoyama, Ichiro; Kenjo, Hironori; Shimokawa, Mototsugu; Kato, Kiyoko
Abstract: Aim: Westernization of lifestyle has increased the numbers of patients with endometrial cancer and obesity. This study aimed to compare the clinical outcomes of robotic‐assisted surgery according to whether patients are obese, morbidly obese, or nonobese. Methods: Sixty‐three patients with endometrial cancer who underwent robotic‐assisted surgery between March 2014 and June 2022 were categorized according to whether they had a body mass index (BMI) <30 (group A, nonobese, n  = 40), ≥30 and <35 (group B, obese, n  = 13), or ≥35 (group C, morbidly obese, n  = 10). Operation time, blood loss, perioperative complications, and recurrence rate were investigated. Results: Conversion to laparotomy was required in one case in group A and one in group C. There was no difference in total operation time, time for setting (including trocar installation and docking of the da Vinci robot), console time, or time for wound closure between the groups; however, there was a significant between‐group difference in the total time for setting and wound closure. There was no significant difference in blood loss or complications between the groups. Three patients in group A and two in group B received adjuvant treatment; none have shown evidence of recurrent disease during a mean observation time of 21 months (range, 2–29). Two cases in group A and one in group B had recurrence during a mean observation time of 38 months (range, 19–46). Conclusion: Patients with endometrial cancer who are obese can be treated safely by robotic‐assisted surgery with a low risk of complications and few relapses.